Achievement of early deep remission is associated with lower rates of weekly dosing for adalimumab-treated patients with crohn's disease: data from extend. (13th March 2011) - Sandborn, W J; Colombel, J F; Lomax, K G; Pollack, P F; Thakkar, R; Camez, A; Chen, N; Yang, M; Chao, J; Mulani, P M
Abstract : Introduction: We explored the relationship between early deep remission and rates of dosage adjustment for patients (pts) with Crohn's disease (CD). Methods: EXTEND studied the effects of adalimumab (ADA) on mucosal healing in pts with moderate to severe ileocolonic CD (CDAI 220–450). Pts received open-label (OL) ADA 160-/80-mg induction therapy at weeks 0/2 and were randomised at week 4 to maintenance therapy with ADA 40 mg every other week (eow) or placebo through week 52. From week 8, pts with flares or non-response could receive OL ADA 40 mg eow. The maintenance regimen could be adjusted to weekly OL ADA for continued flares/non-response. Endoscopic assessments of mucosal disease activity were performed at baseline, week 12 (or unscheduled visits weeks 8–12 prior to switch to OL), time of switch to OL ADA (if after week 12) and week 52 (or early termination). Early deep remission was defined as mucosal healing (visually determined) plus clinical remission (CDAI <150) at week 12. Rates of moving to OL eow and weekly therapy through week 52 were compared between pts randomised to blinded ADA maintenance therapy who achieved week-12 deep remission and those who did not. Results: 64 pts were randomised to ADA maintenance therapy at week 4. ADA-treated pts who achieved deep remission by week 12 had significantly lower rates of dosage adjustment compared with pts not achieving early deep remission (table 1 ). No pts achieving early deep remission moved to weekly therapy. Conclusion: Deep remission, defined as complete mucosal healing plus clinical remission, may be an important treatment goal in CD. Pts in EXTEND who achieved deep remission by week 12 were less likely than those not achieving deep remission to move to OL eow dosing and subsequently receive weekly therapy.